The productive and reproductive performance of indigenous buffaloes at Kawkhali Upazilla, Pirojpur in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The productive and reproductive performance of indigenous buffaloes at Kawkhali Upazilla under Pirojpur district was studied. Fifty seven (57) buffalo owners were interviewed by written interviewed paper from Kawkhali Upazilla under Pirojpur district in 2010.  Out of 57 families 30 containing 45 milch cows, 34 dry cows, 42 heifer calves, 23 bull calves  and 17 bull  which were counted for calculation.  The study demonstrated that the distribution of buffalo populations were scattered and the average buffalo populations were 5.37 per house-holds, age at puberty 45.03 ± 6.97 months, lactation length 242.60±41.46 days, milk yield 2.35±0.703 liters/day, gestation period 317.47±6.57 days, body weight 23.77±5.20 kg/calf, age at first calving 55.33±7.20 months, calving interval 650.93±79.57 days and average post partum heat period was 235.90±52.24 days. These data will be helpful for future research and also give a guideline for buffalo development in Bangladesh.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 161-165